DOP29 Single cell analysis of Crohn's disease fistula; comparison of different locations. (30th January 2023) - Becker drs., M; Koelink, P; Bemelman, W; Buskens, C; Wildenberg, M
Abstract: Background: A common complication of Crohn's disease(CD) are perianal fistulae, highly impacting the quality of life in these patients. The pathogenesis of these fistulas is incompletely understood. Treatment is often given based on knowledge of disease processes in the inflamed intestine itself, but whether the immune activity in the fistula tract is similar remains unknown. Full characterization of the intestinal mucosa versus the fistula tract itself may reveal immunological differences between the two, and generate leads for both development of new interventional options as well as allow better stratification of patients. Methods: Matched biopsies were obtained from the rectal mucosa, the internal opening of the fistula and the tract itself. A total of 30 patients were included (20 CD; 10 non-IBD patients). Tissues were processed to cell suspensions and selected for live CD66b- cells. Single cell RNASeq analysis was performed using 10x Chromium. In total, 111.955 immune cells were annotated and used for analysis. Results: T cells comprised the largest cluster of immune cells, which was subclustered into 19 clusters. Both the internal opening and the fistula tracts contained elevated proportions of effector memory and cycling T cells. Conversely, the rectum contained more central and tissue resident memory cells. T cells expressing IL-22, which were previously described in fistula were detected in considerable number in the rectum and internal opening, but were scarce in the fistula tract itself. These cells were clearly distinct from the IL17A producing subset, and IL17F expressing cells and mainly found in the fistula tracts. Only the tract contained a clear subset of CXCL13 expressing T cells, suggesting follicular helper T cells. Presence of these cells was strongly correlated to the presence of lymphoid inducer cells as well as IgG producing B cells rather than the IgA subset found in the rectum. Clusters of myeloid cells were largely derived from the fistula tracts. Subclustering into 10 clusters indicated a shift from anti-inflammatory to pro-inflammatory macrophages in the tracts compared to the rectal mucosa. Finally, a striking difference in NK cells subsets was observed, with significantly more CD56bright NK cells present in the rectal samples while the internal opening and the tracts were comparable. Conclusion: Cellular composition and activity of the immune cell compartment differs considerably between the rectum, the internal opening of the fistula and the tract. Subsequently, therapy targeted at processes involved in mucosal inflammation may not actually target the fistula itself, which may explain the low success rate in fistula resolution. Careful analysis of the fistula may help to identify targets useful in the treatment.